2022
DOI: 10.1111/jcpe.13716
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of dental implants in patients with and without history of periodontitis: A 20‐year prospective study

Abstract: Aim: To present the 20-year clinical outcomes of tissue-level implants in partially edentulous patients previously treated for periodontitis and in periodontally healthy patients (PHP). Material and Methods:The original population consisted of 149 partially edentulous patients consecutively enrolled in a private specialist practice and divided into three groups: PHP, moderately periodontally compromised patients (mPCP) and severely PCP (sPCP). After successful completion of periodontal/implant therapy, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 32 publications
6
41
0
Order By: Relevance
“…The use of osseointegrated dental implants has become a standard for the prosthetic rehabilitation of fully and partially edentulous patients, providing excellent longterm functional and esthetic outcomes [1][2][3][4][5]. Where necessary, to optimize the repair of dental bone defects and to adequately support implants, a wide variety of bone graft materials have been developed and are available on the market [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of osseointegrated dental implants has become a standard for the prosthetic rehabilitation of fully and partially edentulous patients, providing excellent longterm functional and esthetic outcomes [1][2][3][4][5]. Where necessary, to optimize the repair of dental bone defects and to adequately support implants, a wide variety of bone graft materials have been developed and are available on the market [6].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this decision, future prosthodontic treatment options to restore function and esthetics should be considered. For the restoration of single-tooth gaps, conventional treatment options such as xed dental prostheses (FDPs) [3][4][5], resin-bonded xed dental prostheses (RBFDPs) [6-8] and implant-retained restorations [3,[9][10][11][12][13] have been established in daily dental routine. Usually, at this clinical state, teeth have already been removed or are expected to be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term clinical study conducted over 20 years, concerning dental implants in patients with and without a history of periodontitis, showed that implants, placed after periodontal treatment and supportive periodontal care, yield favorable long-term results. However, patients with a history of periodontitis and non-compliance with supportive periodontal care are at higher risk of biological complications and implant loss [ 21 ].…”
Section: Introductionmentioning
confidence: 99%